Socio-Religious Analysis Of The Low Level Of Understanding Of Zakat Mal In The Community Of Gondangrejo Village, East Lampung - Imtihanah, Ani Nurul; Ely Elsanti (Journal of Contemporary Applied Islamic Philanthropy, 2025)
Purpose: This research aims to identify the social and religious factors that influence the low understanding of the people of Gondangrejo Village towards zakat mal. Methodology: Using a descriptive qualitative approach, this study involved 30 informants and data were collected through interviews, observation, and documentation. Findings: The results show that the habit of attending recitations that focus on zakat fitrah, limited social arena, and low education lead to the lack of understanding about zakat mal. Analysis using Pierre Bourdieu's theory highlights the influence of habitus, arena and capital in shaping this understanding. This study suggests reforming recitation materials, counseling on zakat mal by zakat institutions, and improving religious education to improve people's understanding of zakat mal.